Primitive neuroectodermal tumor (PNET) of the lung in an adult woman - Gachechiladze, Mariam (World J Surg Oncol, 2014)
Primary primitive neuroectodermal tumors (PNETs) are extremely rare in the lung and especially in adult women. We describe a case of PNET of the lung with aggressive behavior in 31-year-old woman. Diagnosis was based on histopathological and immunohistochemical studies, and confirmed by molecular genetic analysis of chromosome rearrangements in the EWSR1 gene region. Clinical follow-up, post-mortem findings, and differential diagnosis are also discussed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1477-7819-12-374) contains supplementary material, which is available to authorized users.